2021
DOI: 10.3389/fimmu.2021.772511
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Cross-Reactive Antibody Responses Do Not Significantly Impact Inactivated COVID-19 Vaccine-Induced Neutralization

Abstract: Recent exposure to seasonal coronaviruses (sCoVs) may stimulate cross-reactive antibody responses against severe acute respiratory syndrome CoV 2 (SARS-CoV-2). However, previous studies have produced divergent results regarding protective or damaging immunity induced by prior sCoV exposure. It remains unknown whether pre-existing humoral immunity plays a role in vaccine-induced neutralization and antibody responses. In this study, we collected 36 paired sera samples from 36 healthy volunteers before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Given the wide spread of sCoVs among the populations, we investigated whether prior sCoVs infection would impact the immunogenicity of the inactivated COVID-19 vaccine. Consistent with one previous study ( 36 ), our findings indicated that sCoVs antibody levels scarcely affected the neutralizing antibody titer induced by the inactivated vaccine, suggesting that immune imprinting induced by prior sCoVs infection did not appear to be a major factor affecting the immunogenicity of inactivated COVID-19 vaccine. This may be attributed to the distribution of cross-reactive epitopes between sCoVs and SARS-CoV-2, as pre-existing cross-reactive antibodies triggered by sCoVs infections primarily target non-neutralizing sites of SARS-CoV-2 ( 19 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…Given the wide spread of sCoVs among the populations, we investigated whether prior sCoVs infection would impact the immunogenicity of the inactivated COVID-19 vaccine. Consistent with one previous study ( 36 ), our findings indicated that sCoVs antibody levels scarcely affected the neutralizing antibody titer induced by the inactivated vaccine, suggesting that immune imprinting induced by prior sCoVs infection did not appear to be a major factor affecting the immunogenicity of inactivated COVID-19 vaccine. This may be attributed to the distribution of cross-reactive epitopes between sCoVs and SARS-CoV-2, as pre-existing cross-reactive antibodies triggered by sCoVs infections primarily target non-neutralizing sites of SARS-CoV-2 ( 19 , 30 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that pre‐existing antibodies, viral protein‐binding B cells, breadth of B cell epitopes, or spike‐specific CD4 + T cells had little impact on the inactivated vaccine‐induced neutralization. Consistently, a previous report on inactivated COVID‐19 vaccines showed that pre‐existing B cell responses detected by mapping B cell epitopes covering the whole sequence of SARS‐CoV‐2 did not significantly affect the neutralizing activity 35 . These results indicate that inactivated‐vaccine‐induced humoral immunity may poorly benefit from pre‐existing immunity to SARS‐CoV‐2.…”
Section: Discussionsupporting
confidence: 87%
“…Consistently, a previous report on inactivated COVID-19 vaccines showed that pre-existing B cell responses detected by mapping B cell epitopes covering the whole sequence of SARS-CoV-2 did not significantly affect the neutralizing activity. 35 These results indicate that inactivatedvaccine-induced humoral immunity may poorly benefit from preexisting immunity to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 93%
“…Depending on the material of the slide carrier, the array can accommodate from a range of from thousands to three million distinct linear peptides. This approach has greatly enhanced the assay sensitivity, enabling early diagnosis of diseases for Lyme disease, Acute Flaccid Myelitis, and others [47][48][49][50]. Another technique, VirScan, integrates high-throughput DNA oligo synthesis, bacteriophage display, and nextgeneration sequencing to achieve antibody profiling.…”
Section: Antibody-based Detectionmentioning
confidence: 99%